Application of Narrative Structure Vladimir Propp and Edmund Burke Feldman of Hornbill Symbol Through Ensera Wat Bujang Sugi Folklore - Florene Ejot, Masanat; Musdi, Shanat (UNIMAS Publisher, 2025)
This research was conducted to examine the effectiveness of Vladimir Propp's narrative structure and Edmund Burke Feldman theory on the Hornbill symbol through folklore of Ensera Wat Bujang Sugi. The method used in this study is based on the morphological theory of Vladimir Propp and Edmund Burke Feldman theory as a second. The objective of this study is to carry out an academic study on how the narrative structure of Vladimir Propp and Feldman theory implemented toward Hornbill symbol in the folklore of Iban Ensera Wat Bujang Sugi. To analyze the data, the researcher classified the scene according to 3 important elements, namely setting, character and theme. 4 experts in Iban folklore and 4 visual artists were interviewed. Data collection was conducted from interviews and documentation. The study uses descriptive qualitative methods and narrative analysis.